The Impact of Regulatory Changes on Foreign Investment in the Transition from Contracts of Work and Coal Mining Venture Agreements to Special Mining Business Licenses - Sumartono, Sumartono; Redi, Ahmad (Asian Journal of Social and Humanities, 2025)
Foreign investment plays a crucial role in supporting Indonesia's economic growth, especially in strategic sectors such as mineral and coal mining, which contribute extensively to state revenues and job creation. As a sector with a high dependence on capital and technology, the presence of foreign investors is a primary factor in driving the exploration, production, and processing of natural resources. This study seeks to evaluate the extent to which legislative protection is provided to foreign investment in the mining sector, especially in the transition from the Work Contract (KK) and Coal Mining Business Work Agreement (PKP2B) to the Special Mining Business License (IUPK). By using normative legal research methods through a literature approach, this study examines various key regulations governing foreign investment in the mining sector, including the cooperation required between foreign investors and domestic capital. The research findings show that the regulatory transition policy has changed the dynamics of foreign investment in this sector, especially with the divestment obligations and cooperation requirements with national business entities, which aim to increase government control and encourage the independence of the domestic mining industry. However, the existing regulations that serve as basic guidelines for foreign investment remain challenging, as legal uncertainty, dynamic policy changes, and advanced fiscal burdens continue to be core issues for foreign investors in maintaining the stability and sustainability of their businesses in Indonesia.